Pengaruh Kecerdasan Emosional Sumber Daya Manusia Terhadap Produktivitas Perusahaan - Mawarti Mawarti; Ibnu Waseu (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
One way to produce good representative performance is to have satisfactory scientific knowledge. Ability has an impact on employee performance. Skills and knowledge are not the only components of ability. Capacity as information can be framed through training and experience, while ability is formed from training. One of the abilities that can be monitored by workers themselves is the ability to appreciate individuals deeply. The ability to appreciate people more deeply can help someone utilize their mental capacity (information) according to their greatest potential. Emotional intelligence needs to be cultivated in order to maximize its potential in boosting employee performance. This research aims to determine the potential impact of emotional intelligence in human resources on the quality and quantity of a company's output.